Involvement in Subject Learning Scale (ISLS) - Bujold, Neree; Saint-Pierre, Henri; Bhushan, Vidya (Canadian Journal of Higher Education, 1997)
Since 1984, when the American Department of Education published a report on higher education entitled "Involvement in learning, realizing the potential of American higher education," many studies have been conducted on this subject pertaining mainly to academic involvement and, a wide-range concept of involvement in learning. It is proposed here to limit the scope of this concept to involvement in subject learning as an easier bounded concept. The Involvement in Subject Learning Scale (ISLS) was therefore constructed and validated and is presented here with its psychometric characteristics. This scale is proposed as an educational outcome measure for research purposes on the quality of instruction in higher education.